2020
DOI: 10.1002/adbi.202000012
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel Micropost Arrays with Single Post Tunability to Study Cell Volume and Mechanotransduction

Abstract: with both physical signals and constraints. Mesenchymal stromal cells (MSCs) have served as an important model cell type to understand how physical properties of the ECM impact cell size and functions because they are highly mechanosensitive. On 2D substrates, matrix elasticity is known to mediate MSC volume by water flux. [2] Matrix elasticity also activates nuclear translocation of Yes-associated protein (YAP) in MSCs, [3] which is known to regulate cell volume. [4] In this context, the ability of cells to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…We assessed if FAK was required to soften EC to maintain lung homeostasis. We used atomic force microscopy (AFM) to quantify intracellular tension, i.e., Young's modulus (E) in control inactivated versus FAK depleted EC (Discher et al, 2005;Wong et al, 2020). We found that inactivated EC generates physiologically relevant intracellular EC tension ⁓8 KPa (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We assessed if FAK was required to soften EC to maintain lung homeostasis. We used atomic force microscopy (AFM) to quantify intracellular tension, i.e., Young's modulus (E) in control inactivated versus FAK depleted EC (Discher et al, 2005;Wong et al, 2020). We found that inactivated EC generates physiologically relevant intracellular EC tension ⁓8 KPa (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The intended purposes of AMFIP to study dynamic, multi-faceted, and long-term biological questions are achieved by demonstrating the previously unknown relationship between YAP dynamics and cell mechanics. We think AMFIP is a reliable platform with proven advantages over existing alternatives and validated long-term utility that will benefit the scientific community in multidisciplinary biomedical research [34,37,54,[64][65][66][67][68][69][70][71]. The charge-free source code of AMFIP is available to the public on GitHub (link: https://github.com/njheadshotz/AMFIP), and we hope researchers will develop and expand more new functions based on AMFIP to enhance their specific automatic operations in research.…”
Section: Discussionmentioning
confidence: 99%
“…To covalently bond cross-linked PEG-DA hydrogel to a thin glass surface, acrylate groups were attached to glass coverslips by silanization as described . A solution of 3% v / v 3-(trimethoxysilyl)­propyl acrylate (TCI Chemicals) and 5% v / v glacial acetic acid (Fisher Scientific) was prepared in methanol.…”
Section: Methodsmentioning
confidence: 99%